THE EFFECT OF PERCEPTION AND VALUE OF CAR CONSUMER BUYING DECISIONS IN MANADO CITY - Manggaribet, Mario B.; Kawet, Lotje; Moniharapon, Silcyljeova (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Competitive advantage in a global scale is owned by the company, in which companies are required to be able perform a better process in order to produce high quality goods or services which are copetitive andhave a reasonable price. This study aims to investigate theeffect of perceptions and costumer value to consumer demand at Car Dealers in Manado. The type of this research is associative research and Multiple Linear Regression analysis techniques, in wich, the number samples is 100 respondents. The results showed that perceptions and costumer value significantly influence consumer demand at Car Dealers in Manado. Byconsidering that the competition in the car business is getting tougher for companies, it is suggested to increase product quality by doing continuous innovation and fufilling the ever-changing consumer wants. Keywords: consumer perceptions, customer value, consumer demand